Ancient Burial Mounds Provide Safe Havens for Grassland Specialist Plants in Transformed Landscapes—A Trait-Based Analysis - Deák, Balázs; Rádai, Zoltán; Bátori, Zoltán; Kelemen, András; Lukács, Katalin; Kiss, Réka; Maák, István Elek; Valkó, Orsolya (Frontiers in Ecology and Evolution, 2021)
Due to the intensified land use in transformed landscapes, grassland biodiversity is often restricted to habitat fragments inadequate for arable use or for urban development. In conti-nental parts of Eurasia, the approximately 600,000 ancient burial mounds (called ‘kurgans’) built by nomadic tribes of the steppes are amongst the most widespread landmarks providing refuge for dry grassland species. In our study by using plant functional groups and functional traits, we aimed at gaining insight into the ecological and evolutionary processes shaping the structure and the composition of assemblages of grassland specialist plant species on kur-gans embedded in the agricultural landscapes of East-Hungary. As a comparison, we also studied roadside verges and pristine extensive grasslands in the same region. We found that despite their small size, due to the lack of human disturbances and high microhabitat diver-sity kurgans can maintain a high species richness and percentage cover of specialists, espe-cially when compared to verges. We revealed that assemblages of specialist plants on kur-gans are characterized by traits typical to terrestrial habitat islands such as self-compatibility, large seed mass and tall stature. Kurgans and extensive grasslands were char-acterized by higher functional diversity (both at the level of single traits and multi-trait based functional dispersion) which is probably due to the higher level of environmental het-erogeneity compared to the homogeneous environment in verges.